面向印尼中级汉语学习者的指人缀词研究 - S Sunarti; Zeng Liying (Journal of Chinese Language and Culture Studies, 2022)
Abstract: This paper research the 10 personal’s Chinese semi-affixes such as “人, 鬼, 汉, 师, 家, 生, 手, 星, 员, 长, among the intermediate phase of the Chinese Department State University of Surabaya in Indonesia in the form of questionnaires. At the same time, the condition of Indonesian students personal’s semi-affixes in the Chinese language was analyzed. This paper finds that within 10 Chinese personal’s semi-affixes mentioned, Indonesian students in the intermediate phases have mastered the personal’s semi-affixes: “师”, “员”, and “长”and the intermediate Indonesian students find “鬼”, “家” and “星” were most difficult. 摘要: 本文以印度尼西亚泗水国立大学中文系中间阶段中的“人、鬼、汉、师、家、生、手、星、员、长”等10个指人词缀的形式进行研究。 同时，对印尼学生汉语个人半词缀的情况进行了分析。 本文发现，在提到的10个中文指人词缀中，中级阶段的印尼学生已经掌握了指人词缀：“师”、“员”、“长”。 印尼中级学生觉得“鬼”、“家”、“星”最难。